2009
DOI: 10.1128/jb.01567-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Potassium Uptake Systems in Sinorhizobium meliloti Osmoadaptation and Symbiotic Performance

Abstract: Stimulation of potassium uptake is the most rapid response to an osmotic upshock in bacteria. This cation accumulates by a number of different transport systems whose importance has not been previously addressed for rhizobia. In silico analyses reveal the presence of genes encoding four possible potassium uptake systems in the genome of Sinorhizobium meliloti 1021: Kup1, Kup2, Trk, and Kdp. The study of the relevance of these systems under a number of different growth conditions and in symbiosis showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
(35 reference statements)
2
39
0
Order By: Relevance
“…Transport functions include a kdpABCD operon, encoding one of the four predicted potassium uptake systems (14), as well as the actP and hmrR genes, involved in copper expulsion. A gene that might be involved in selenocysteinetRNA formation (selA) was also found.…”
Section: Resultsmentioning
confidence: 99%
“…Transport functions include a kdpABCD operon, encoding one of the four predicted potassium uptake systems (14), as well as the actP and hmrR genes, involved in copper expulsion. A gene that might be involved in selenocysteinetRNA formation (selA) was also found.…”
Section: Resultsmentioning
confidence: 99%
“…The L. interrogans genome encodes homologs of the Kdp and Trk-like Ktr potassium transporters (58,59). Disruption of genes encoding Trk, Ktr, and Kdp transporters attenuates growth of diverse bacteria during osmotic stress (60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%
“…During this process, an exchange of molecular signals occurs between the two partners, leading to the formation of the root nodule, where biological nitrogen fixation takes place (12). It has been observed that rhizobium mutants affected in adaptation to high salinity present deficiencies in their symbiotic capacity (27,7,25). These results emphasize the importance of studying the adaptation mechanisms of rhizobia to osmotically unbalanced environmental conditions.…”
mentioning
confidence: 99%
“…Rhizobia may use distinct mechanisms in response to hyperosmotic conditions, such as stimulation of potassium uptake (7), changes in cell morphology and size, or modifications in the pattern of extracellular polysaccharides (18,35,42). Nevertheless, one of the most general responses for long-term adaptation to osmotic stress is the intracellular accumulation of osmoprotective compounds (24,45).…”
mentioning
confidence: 99%